Magnetotransport and magnetocrystalline anisotropy studies of gallium manganese arsenide thin films - King, Christopher Stuart (2008)
The ferromagnetic semiconductor gallium manganese arsenide is an important test-bed material for spintronics applications. Whilst a Curie temperature anywhere close to room temperature has yet to be demonstrated, the excellent micromagnetic properties, simple band structure and unusual combination of having both low moment densities and high spin-orbit coupling make this an interesting material to study from both theoretical and experimental perspectives.